2017
DOI: 10.3389/fncir.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Delta-Gamma Phase-Amplitude Coupling in the Prefrontal Cortex of Behaving Rats

Abstract: Dopamine release and phase-amplitude cross-frequency coupling (CFC) have independently been implicated in prefrontal cortex (PFC) functioning. To causally investigate whether dopamine release affects phase-amplitude comodulation between different frequencies in local field potentials (LFP) recorded from the medial PFC (mPFC) of behaving rats, we used RuBiDopa, a light-sensitive caged compound that releases the neurotransmitter dopamine when irradiated with visible light. LFP power did not change in any frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 64 publications
5
25
2
Order By: Relevance
“…More generally, these physiological oscillations are considered to be fundamental to the relation of brain structure and function 20 . Phase-amplitude coupling of delta/beta and theta/gamma oscillations has also been reported in motor and somatosensory cortices of rodents 94,59,144,4 and primates 118,32,90 . Cross-frequency coupling may help integrate information across temporal scales and across networks 21 .…”
Section: Emergence Of Physiological Oscillations and Phase-amplitude mentioning
confidence: 76%
“…More generally, these physiological oscillations are considered to be fundamental to the relation of brain structure and function 20 . Phase-amplitude coupling of delta/beta and theta/gamma oscillations has also been reported in motor and somatosensory cortices of rodents 94,59,144,4 and primates 118,32,90 . Cross-frequency coupling may help integrate information across temporal scales and across networks 21 .…”
Section: Emergence Of Physiological Oscillations and Phase-amplitude mentioning
confidence: 76%
“…The mPFC has direct projections from the hippocampus and works with the neural information coming from the hippocampus to perform its functions [14]. Previous studies show a dominant delta oscillation in mPFC which is modulated by task demand [15] and also by the activity in the hippocampus [16]. However, the exact mechanisms in which they communicate are not yet fully understood.…”
Section: Delta and Gamma Oscillations In Medial Pre-frontal Cortexmentioning
confidence: 99%
“…Indeed, it was previously shown that ketamine could affect CFC between theta and gamma oscillations in the hippocampus of freely moving rats 51 . In contrast, delta-gamma CFC has been described in corticostriatal network and could reflect cortico-mesolimbic connectivity 55 , induced in frontal regions by anesthetic doses of ketamine 56 and modulated by dopaminergic activation 57,58 . One possible mechanism by which KET produces an enhancement in CFC is by increasing extracellular levels of dopamine.…”
Section: Discussionmentioning
confidence: 98%